Design of linear steam distillation machine with arduino remote connection via messaging - Arizapana Renojo, Kennil Kevin (2023)
This study aims to design a piece of distillation equipment, with greater efficiency and extraction capacity. Currently, there are steam distillation machines, most of these equipment has the capacity to distill between 1 to 100 kilograms of material. In the present design, a linear vapor trace distillation is applied, with a capacity to distill 200 kilograms of schinus "molle"; on the other hand, the equipment will have connection to a mobile phone through Arduino, from which it will be possible to make emergency stops. This research was obtained through calculations showing that 1.89 liters of essential oil can be extracted from every 200 kilograms of molle. Finally, it is concluded that the current still is theoretically more efficient, extracting much more oil than the other still. Also, it has the capacity to distill all those roots, stems, leaves, flowers, and seeds that have an essence.